Mengkaji Program Padi Tanam Sabatang (Pts) dari Kaca Mata Teori Difusi Inovasi - Fitriani, Lili (Universitas Islam Negeri Imam Bonjol Padang, 2013)
Pengelolaan Tanaman Terpadu (PTT) or better known as a Paddy Cultivation (Padi Tanam Sabatang/PTS) is an flagship program of the Ministry of Agriculture in order to self-sufficiency in West Sumatra. This program was introduced on 2007. Since the program was introduced in the last 7 years, there are still a lot of farmers who are interested in applying this technology. Thus, the author is interested in reviewing the PTS program from perspective of the diffusion of innovation theory within communication science.Therefore, the author conducted a qualitative research to examine the issu. Data collection conducted by in-depth interview, observation, and documentation, then presented in descriptive qualitative method.The research concluded that Padang government performs the difusion of innovation by applied conventional mass media and interpersonal media, while the hybrid media has not been used. The medium considered effective is the Field School (Sekolah Lapang/SL). The inhibiting factors are 1). Complexity of the PTS Program, 2). The government has not attempted to perform diffusion programs to to the land owners who are not farmers.